STRATEGI HUMAS PT. KAI PADA MUSIM MUDIK LEBARAN 2022 MELALUI APLIKASI KAI ACCESS - Wahyu Maulida (MEDIAKOM, 2023)
In 2022, Indonesia has entered a new normal from a fairly bad condition due to the covid-19 outbreak that has attacked for almost 2 years. During COVID-19, the Indonesian government implemented a lockdown and implemented Large-Scale Social Restrictions (PSBB). One of the impacts of the policies taken is on the transportation aspect, for example PT KAI. This situation made PT KAI itself take a policy to reduce the train operating schedule and also reduce the passenger quota. In this post-covid condition, PR is collaborating with the marketing team to increase ticket sales. Public Relations is an activity that bridges between companies or institutions with the community. Public relations itself must be able to provide information that can improve the company's image. This research uses qualitative research through literature study and in-depth interviews. The steps for obtaining data are through Data Reduction, Data Display, Drawing Conclusions, and Verification. The theory used in this research is Image Theory. The results of this study show that PT KAI provides a strategy for the 2022 homecoming season through the KAI Access application. Through this strategy, PT KAI itself helps the government to reduce direct contact between people which causes crowds and increases the possibility of the emergence of new variants of COVID. In addition to the strategy carried out by PT KAI, it has caused several obstacles in the community.